THE ANALYSIS OF FACTORS INFLUENCING THE ASEAN-5 TOURISM SECTOR BASED ON AUSTRALIA OUTBOND TOURISM - Petrus Jerry Pardomuan (Jurnal Ilmiah Mahasiswa FEB, 2016)
Tourism Sector is one of the economic sectors that will able to expand in the future because a country cannot rely only on exploiting the natural resources. Many studies have been conducted with the aim at investigating the relationship between the tourism performance and macroeconomic variables. However, only a few studies investigated the regional tourism performance based on a specific origin country. This study investigated the relationship between ASEAN-5 international tourism receipts as the dependent variable and macroeconomic variables as the independent variables namely the exchange rates to Australian Dollar, Australia GDP per capita, international tourism expenditure, and transportation costs. The method used to investigate this study is panel data regression model to determine the influence among the explanatory variables to the dependent variable. The results denote that the exchange rates, GDP per capita, and the transportation cost are significant to the tourism receipts. Meanwhile, the international tourism expenditure variable shows an insignificant result to the tourism receipts. Keywords:  Tourism economics, tourism receipts, exchange rate, GDP per capita, international tourism expenditure, transportation cost, panel data regression.